∫ 1/(sin³xcos⁵x) dx = ∫ csc³xsec⁵x dx
= ∫ cscxsec⁵x d(- cotx)
= - cotx · cscxsec⁵x + ∫ cotx d(cscxsec⁵x)
= - csc²xsec⁴x + ∫ cotx · (5sec⁶x - csc²xsec⁴x) dx
= - csc²xsec⁴x + 6∫ cscxsec⁵x dx - ∫ csc³xsec⁵x dx
2∫ csc³xsec⁵x dx = - csc²xsec⁴x + 6∫ cscxsecx · (1 + tan²x)² dx
2∫ csc³xsec⁵x dx = - csc²xsec⁴x + 6∫ cscxsecx · (1 + 2tan²x + tan⁴x) dx
2∫ csc³xsec⁵x dx = - csc²xsec⁴x + 6∫ cscxsecx dx + 12∫ sinx/cos³x dx + 6∫ tan³xsec²x dx
2∫ csc³xsec⁵x dx = - csc²xsec⁴x + 6∫ 1/tanx d(tanx) - 12∫ 1/cos³x d(cosx) + 6∫ tan³x d(tanx)
2∫ csc³xsec⁵x dx = - csc²xsec⁴x + 6ln|tanx| + 12/(2cos²x) + 6 · tan⁴x/4
∫ csc³xsec⁵x dx = - (1/2)csc²xsec⁴x + 3ln|tanx| + 3sec²x + (3/4)tan⁴x + C
经过软件验算正确.